AI in the Criminal Justice System: Fair Trial, Due Process, and Accountability - Muhammad Mehmood Ahmed Klasra (`, 2025)
Artificial Intelligence (AI) in the criminal justice system has great potential to enhance the efficiency and uniformity of decision-making. But its application raises vital questions about fairness, due process and accountability. This essay explores the power of AI in criminal justice and how they relate to predictive policing, sentencing algorithms, and forensic techniques. Using this triangulation to conduct a review of cases, literature and ethical frameworks the paper analyses opportunities and threats of AI in guaranteeing fair trials, due process and accountability. The results indicate that AI could be beneficial for improving the efficiency of the judicial service and harmful in reinforcing biased decisions, being non-transparent and not undergoing scrutiny. The paper closes with suggestions concerning the ethical and responsible use of AI in criminal justice, addressing the importance of transparency, regular auditing, and the protection of human rights.